Sediment scouring at the foundation of a coupled wind and wave device: a numerical study - Chen, Xin; Yu, Xiang; Dong, Xiaochen; Xu, Chuanli; Liu, Zhen; Wang, Lihui (Frontiers in Marine Science, 2025)
IntroductionDeveloping wind-wave coupled devices is becoming a research hotspot in offshore renewable energy. While previous studies have primarily concentrated on the hydrodynamic performance of such devices, few have addressed sediment scouring near the foundation, which is critical to their safety.MethodsTherefore, based on the design of a wind-wave coupled device integrating an offshore fixed wind turbine, a sediment scouring model is developed using the commercial computational fluid dynamics platform Flow-3D®. The numerical model is validated using experimental test data, and the sediment scouring and deposition under the combined effects of waves and currents are investigated.ResultsThe results indicate that the oscillating water column tube array can expand the scouring area but have a minor influence on the maximum scouring depth. In addition, due to the sheltered effect of the oscillating water column tubes, the maximum scouring depth near the piles at the far end can be reduced.DiscussionBy optimizing the distance between the tube ends and the seabed, the maximum scouring depth can be reduced by 22.8%, which is beneficial to the safety and stability of the foundation of the coupled device. The key findings of this study provide a more comprehensive design basis for the development and engineering practice of the wind-wave coupled device.